Explanation:
To find out y intercept of any function, we plug in 0 for x and solve for y
For any function y=ab^x + c
The horizontal asymptote at y=c
Now we check each function
Plug in 0 for x to find y intercept
y intercept at (0,-3)
Horizontal asymptote at y=c , here c= -4
So horizontal asymptote at y = -4 and y intercept at (0,-3)
Plug in 0 for x to find y intercept
y intercept at (0,13)
Horizontal asymptote at y=c , here c= 4
So horizontal asymptote at y = 4 and y intercept at (0,13)
Plug in 0 for x to find y intercept
y intercept at (0,5)
Horizontal asymptote at y=c , here c=-4
So horizontal asymptote at y = -4 and y intercept at (0,5)
Plug in 0 for x to find y intercept
y intercept at (0,5)
Horizontal asymptote at y=c , here c= 4
So horizontal asymptote at y = 4 and y intercept at (0,5)